The kinematic analysis of the straight punch in two ways for amateur boxing players in Jordan - Raf’at Ald’ily, Ra’fat Omar; Abu-Shihab, Esam Najeh; Ibrahim Abualtaieb, Mohammad Hassan; Alharahsha, Qutaiba A.; Abu Aloyoun, Ala’a Kh.; Altarawneh, Orouba Dheeb; Mohammad Alyasen, Qusai Basem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to identify some kinematic variables (distance between the feet, arm movement, punch speed, punch time, punch distance, ankle angle, knee angle, elbow angle, shoulder angle, pelvis angle) for the straight punch between two methods. The first method: performing a straight punch with the right hand towards the target without changing the distance between the feet and being on a straight line. The second method: performing a straight punch with the right hand towards the target without changing the distance between the feet, and the left foot is ahead of the right foot. A total of 8 amateur boxers in Jordan who were photographed using an iPhone camera at a frequency of 60 frames per second, participated in this study. The researchers downloaded videos on a computer (LAPTOP), which contains the Kinovea software (Kinovea. Setup.0.8.15.), and determined the best attempts for each player by watching the videos. Then, the researchers analyzed the attempts through the kinetic analysis program (Kinovea. Setup.0.8.15.) and extracted the study variables. The shorter the muscle contraction time of the straight punch, the greater the kinetic momentum and speed of the punch in both styles, and the greater the knee angle, the greater the punch and speed of the punch in both styles. Also, momentum and punch speed were better in the second method. We recommend a climatic and other clinical study of the straight stroke. We also recommend to use the second method in the straight punch.